Associated Topics || Dr. Math Home || Search Dr. Math

### Parametric Equations

```
Date: 07/21/98 at 19:15:19
From: Ivan Li
Subject: Paramatric equations

I hope you can help me with this question.

A) A curve is given parametrically by the equations:

x = (3 - 2k)^2   and  y = (2 + k)^2

(i) Find dy/dx in terms of k and hence find the point on the curve
at which the tangent is parallel to the  y-axis.

(ii) Find the x-intercept of the curve and the equation of the normal
at this point.

(iii) Find point of intersection between the curve and another curve
defined parametrically by the equations:

x = 4/p + 4  and  y = (p + 1)/p

B) Find the cartesian equation of the curve which is defined
parametrically by:

x = cosec(t + pi/2)  and  y = tan (t + pi/4)
```

```
Date: 07/22/98 at 11:04:40
From: Doctor Anthony
Subject: Re: paramatric equations

Problem A(i):

dy/dk     2(2+k)        2+k
dy/dx =  ----- = ----------- = --------
dx/dk   2(3-2k)(-2)   -2(3-2k)

2+k
dy/dx = -----
4k-6

The graph is parallel to the y-axis when 4k-6 = 0. Thus k = 3/2.
Then x = (3-3)^2 = 0 and y = (7/2)^2 = 49/4

The curve is parallel to y axis at the point (0, 49/4).

Problem A(ii):

At y = 0, k = -2 and then x = (3-2k)^2 = (3+4)^2 = 49.
So the x-intercept of curve is the point (49,0).

The slope of curve at this point is 0, and so the normal is the line
x = 49.

Problem A(iii):

At the point of intersection:

(3-2k)^2 = 4/p + 4  = 4(1 + p)/p    and

(2+k)^2 =  (p + 1)/p

Dividing these equations we get:

(3-2k)^2
-------- = 4
(2+k)^2

Taking square roots:

3-2k
---- = +/- 2
2+k

Taking positive value first, we find:

3-2k = 2(2+k)
3-2k = 4+2k

Thus:

4k=-1
k = -1/4

Putting this value into expressions for x and y in terms of k we get
one point of intersection.

Taking negative value:

3-2k = -2(2+k)
3-2k = -4-2k

Since this equation has no solution, there is just one point of
intersection, given by k = -1/4

Problem B:

First note:

x = cosec(t+pi/2) = sec(t)
y = [tan(t) + tan(pi/4)]/(1-tan(t)) = [1+tan(t)]/[1-tan(t)]

Multiply top and bottom by 1+tan(t):

y = [1+tan(t)]^2/[1-tan^2(t)]
y = [1+2tan(t)+tan^2(t)]/[1-tan^2(t)]

We have x^2 = sec^2(t) = 1+tan^2(t), so:

tan^2(t) = x^2 - 1
tan(t) = sqrt(x^2-1)

Thus:

1 + 2 sqrt(x^2-1) + x^2 - 1     x^2 + 2 sqrt(x^2-1)
y =  ---------------------------  =  -------------------
1 - (x^2 - 1)                  2 - x^2

- Doctor Anthony, The Math Forum
Check out our web site! http://mathforum.org/dr.math/
```
Associated Topics:
High School Calculus
High School Equations, Graphs, Translations

Search the Dr. Math Library:

 Find items containing (put spaces between keywords):   Click only once for faster results: [ Choose "whole words" when searching for a word like age.] all keywords, in any order at least one, that exact phrase parts of words whole words

Submit your own question to Dr. Math
Math Forum Home || Math Library || Quick Reference || Math Forum Search